2015
DOI: 10.1073/pnas.1512144113
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing representations of dynamic visual objects in early visual cortex

Abstract: As raw sensory data are partial, our visual system extensively fills in missing details, creating enriched percepts based on incomplete bottom-up information. Despite evidence for internally generated representations at early stages of cortical processing, it is not known whether these representations include missing information of dynamically transforming objects. Long-range apparent motion (AM) provides a unique test case because objects in AM can undergo changes both in position and in features. Using fMRI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 60 publications
5
34
1
Order By: Relevance
“…In summary, we found activation in early visual cortex corresponding to a dynamically occluded object similar to what has recently been found with apparent motion (Chong, Familiar, and Shim 2015; Larsen, Madsen, Lund, and Bundesen 2006; Muckli et al 2005; Sterzer, Haynes, and Rees 2006). However, when the object instantly disappeared instead of becoming gradually occluded, there was no evidence of corresponding activation in the occluded quadrant.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…In summary, we found activation in early visual cortex corresponding to a dynamically occluded object similar to what has recently been found with apparent motion (Chong, Familiar, and Shim 2015; Larsen, Madsen, Lund, and Bundesen 2006; Muckli et al 2005; Sterzer, Haynes, and Rees 2006). However, when the object instantly disappeared instead of becoming gradually occluded, there was no evidence of corresponding activation in the occluded quadrant.…”
Section: Resultssupporting
confidence: 86%
“…This stands in contrast to several other studies of representations along the apparent motion path that have found increased activity in early visual cortex (Goebel et al 1998; Larsen et al 2006; Maus et al 2010; Muckli et al Singer 2005; Seghier et al 2000; Sterzer, Haynes, and Rees 2006; Wibral et al 2008). However, a similar lack of activation was also observed in a recent study of representations along the apparent motion path (Chong, Familiar, and Shim 2015). The use of circle and star stimuli was intended to minimize the contribution of orientation-specific horizontal processing within and between early visual areas including V1 (Field, Hayes, and Hess, 1996; Frégnac et al 2010; Gilbert et al 1996; Seriès et al 2002; Seriès, Lorenceau and Frégnac 2003).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Feed-forward representations in V1 are of a high spatial resolution, but feedback to V1 is less spatially precise [26] and contains higher-level (more abstract) representations of stimulus spaces [66]. This computation of sensory inputs with top-down influences depends on the instruction of the top-down signal; for example, feedback can reconstruct an absent feedforward stimulus [67,68], enhance an illusory feedforward input [69] or suppress a predictable stimulus [70]. We do not know yet how these two streams of representation are combined in V1, but assume that both are constrained by retinotopy.…”
Section: The Singularity Of Primary Visual Cortexmentioning
confidence: 99%
“…However, when internal models are fed back to sensory cortex, we assume that they are translated into sensory predictions that would intuitively have simpler content. In PNAS, Chong et al (3) provide empirical evidence needed to drive this theory forward. Using brain reading, they show that the brain constructs new plausible predictions of expected sensory input, and that these predictions can be read out in sensory cortex.…”
mentioning
confidence: 99%